An analysis of the knowledge of adults aged between 18 and 45 on HPV along with their attitudes and beliefs about HPV vaccine: the Cyprus case - Filiz Yarıcı; Betül Mammadov (BMC, 2023)
Abstract Background The aim of this research is to analyze knowledge of adults between 18 and 45 years of age and living in the Northern Cyprus about Human Papilloma Virus (HPV) along with their attitudes and beliefs towards HPV vaccine. Materials and methods The research, which was planned as a descriptive and cross-sectional, was executed on the web. The research was completed with 1108 women and men adults between 18 and 45 years of age, living in the Northern Cyprus and volunteered to participate in the study. Results 51.90% of the adults participating in the study were found to be women, 8.84% had a Sexually transmitted disease (STD) before and 63.27% of the individuals who had a sexually transmitted disease before also had had HPV and they knew it, 77.55% had undergone a treatment for their disease, 59.18% were found to be actively infected with HPV. Statistically significant and positive correlations were determined between the overall scores of the participants from the Human Papillomavirus Knowledge Questionnaire (HPV-KQ) and their scores in the perceived severity, perceived benefits and perceived susceptibility sub-dimensions of the Health Belief Model Scale for Human Papilloma Virus and Its Vaccination (HBMS-HPVV) (p < 0.05). There was a statistically significant and negative correlation between HPV-KQ scores, questions on Current HPV Vaccination Program and the perceived barriers sub-dimension of the HBMS-HPVV whereas there was a statistically significant and positive correlation between the HPV-KQ scores, questions on Current HPV Vaccination Program and the perceived benefits and perceived susceptibility sub-dimensions of the HBMS-HPVV (p < 0.05). Conclusions It has emerged that the participants do not have enough information about HPV, they do not know the ways and symptoms of protection from HPV, they do not have enough information about early diagnosis and screening, and they know very little about the HPV vaccine. Health policies should be developed to increase the awareness of individuals about HPV, to increase education and to provide free vaccines.